1998
DOI: 10.1111/j.1398-9995.1998.tb03923.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral allergy syndrome to grapes

Abstract: ACKNOWLEDGMENTWe thank the agronomist Dr Carlo Colella for his valuable technical assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Although IgE-mediated hypersensitivity to grapes has been considered an uncommon problem [3], often associated with oral allergy syndrome reactions [26,27,28], we describe a group of 37 children and young adults, who had faced one or more severe reactions after the consumption of grapes. This cohort suggests that grape allergy may not be a trivial problem requiring epidemiological evaluation as well as elucidation of the mechanisms involved in terms of primary sensitisation, occurring symptoms, molecular structure and cross-reactions as well as clinical relevance of allergens involved in allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although IgE-mediated hypersensitivity to grapes has been considered an uncommon problem [3], often associated with oral allergy syndrome reactions [26,27,28], we describe a group of 37 children and young adults, who had faced one or more severe reactions after the consumption of grapes. This cohort suggests that grape allergy may not be a trivial problem requiring epidemiological evaluation as well as elucidation of the mechanisms involved in terms of primary sensitisation, occurring symptoms, molecular structure and cross-reactions as well as clinical relevance of allergens involved in allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients reported with grape allergy did not tolerate any grape species, wine or raisins [3,4,5,6,7,8]. Only 1 patient seems to have a grape allergy specific to a certain Americana blue grape but tolerance to other grapes [3].…”
Section: Discussionmentioning
confidence: 99%
“…Grapes grown in temperate and subtropical areas on all continents are widely consumed as fresh fruit, juice and wine. However, allergy to grapes has been rarely reported [3,4,5,6,7,8]. In a recent study, endochitinase 4, LTP Vit v 1 (accession No.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown a possible relation between allergic reactions to grapes and other fruits. 2 Sensitisation to apple, peach, cherry, and banana was also investigated using prick-to-prick tests. Investigation of atopy using skin prick tests with 10 commercial allergens was not possible on all employees due to the production schedule of the winery.…”
Section: Methodsmentioning
confidence: 99%